Encephalic xanthomas in a large malayan chevrotain (Tragulus napu) - González, María F.; Sisó, Silvia; Pardo, Ingrid D.; Carvallo, Francisco R. (Austral Journal of Veterinary Sciences, 2017)
An adult water chevrotain was euthanized due to severe non-responsive pododermatitis. Incidentally, multiple to coalescing cholesterol granulomas were identified within the right diencephalon, characterized by the presence of foamy macrophages and cholesterol clefts consistent with encephalic xanthomas. No clinical signs or predisposing conditions associated with this finding were identified. This is the first known report of encephalic xanthomas in this species.